PROGRAM PENYULUHAN PENGENTASAN PENGGUNA ROKOKANAK USIA SEKOLAH - Sumedi P Nugrah (Asian Journal of Innovation and Entrepreneurship, 2013)
The number of cigarette users adolescents and adults in the hamlet CangkolDuwur, Lencohmakes the author feel sad. Moreover, there are some primary schoolage children that I know is based on interviews also been using cigarettes.Tobacco useeither in adults, adolescents or children actually many a devastating effect, not only forthe active smoker but also for others who are exposed to smoke from these cigarettes.Seeing this, the author then took the initiative to do counseling to children early age notto smoke for those who do not smoke and those who already smoke to quit smoking.This activity is held with a more relaxed approach considering the object of thisextension are children hamlet Cangkol Duwur who are not familiar with things that aretoo formal. The program spent 6 hours with a total of 3 times meeting.